2011
DOI: 10.1016/j.physleta.2011.04.038
|View full text |Cite
|
Sign up to set email alerts
|

On the interband pairing in doped graphane

Abstract: An estimation shows that the interband pairing channel between the valence band components of doped graphane can support a superconducting transition temperature (or a contribution into this expected event) of the order of 100 K at the coupling strength near 1 eV

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Savini et al [ 100 ] used p-doped graphane to fabricate a prototype high-Tc electron–phonon superconductor, which has Tc as high as 150 K for a 1-nm nanowire, higher than copper oxides. Loktev and Turkowski [ 101 ] and Kristoffel and Rägo [ 102 ] considered the superconducting properties of multilayer graphane by taking into account the fluctuations of the order parameter. The result showed that in the single-layer case, the BKT critical temperature which corresponds to the vortex SC is equal to the MF temperature 100 K beginning from a rather low value of doping less than 0.01.…”
Section: Reviewmentioning
confidence: 99%
“…Savini et al [ 100 ] used p-doped graphane to fabricate a prototype high-Tc electron–phonon superconductor, which has Tc as high as 150 K for a 1-nm nanowire, higher than copper oxides. Loktev and Turkowski [ 101 ] and Kristoffel and Rägo [ 102 ] considered the superconducting properties of multilayer graphane by taking into account the fluctuations of the order parameter. The result showed that in the single-layer case, the BKT critical temperature which corresponds to the vortex SC is equal to the MF temperature 100 K beginning from a rather low value of doping less than 0.01.…”
Section: Reviewmentioning
confidence: 99%
“…On the basis of our analysis, we may start to indicate a possible roadmap for the discovery of novel HTS. 16 The conditions for higher temperature superconductivity, or even room temperature superconductivity, might be met in graphene bilayers and graphane, 72,73 where the exchange-like interband interaction could be even stronger than the intraband Cooper pairing, as also predicted for superlattices of carbon nanotubes. 22…”
mentioning
confidence: 97%
“…Atoms replacing C atoms in GA can have large magnetic moments, and may have spintronic applications [8,9]. A high-temperature superconductor has been predicted for p-doped GA [10,11,12]. H-substitution by Ca in GA (replacing H) has good potential as a hydrogen storage material, binding up to 5 H 2 molecules/Ca atom [13].…”
Section: Introductionmentioning
confidence: 99%